Increased risk of mortality from COVID-19 in people with obesity - Ana Cristina Ribeiro; Priscila Poli; Silvia Carla da Silva André Uehara (Rev Rene)
Objective: to analyze the risk of mortality from COVID-19 in people with obesity. Methods: observational, retrospective, and analytical study. Data were collected in the State System of Data Analysis. For the comparative analysis of people with and without obesity, n=168,808 was adopted. The analyses were performed using the log-binomial regression model and relative risk calculation. The comparative model was adjusted for sex, age group, heart disease and diabetes.  Results: in more than 95% of COVID-19 notifications, information regarding the risk factor obesity was recorded as ignored. Obese individuals with COVID-19 had 26% higher risk of death when compared to those without obesity. Obese individuals in the 11 to 60 age groups had the highest mortality risks compared to individuals without obesity. Obese women in the age groups 31 to 50 years and elderly women over 71 years had the lowest mortality risk when compared to obese men. Conclusion: obese people, especially adults, have an increased risk of mortality from COVID-19. Contributions to practice: to help establish public health strategies to identify the profiles of individuals considered at high risk in the SARS-CoV-2 pandemic.